Myocardial integrated ultrasonic backscatter for early detection of cardiac involvement in patients with Wilson disease - Arat, Nurcan; Kaçar, Sabite; Gölbaşı, Zehra; Akdoğan, Meral; Kuran, Sedef (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Videodensitometry is a feasible noninvasive ultrasound tissue characterization method allowing early detection of myocardial changes. This study aimed to investigate ultrasonic backscatter properties of the myocardium in Wilson disease patients. Materials and Methods: We compared cardiologically asymptomatic Wilson disease patients (W group) (n=18) with age-matched (26.7±9.6 years) healthy controls (C group) (n=15). Diagnosis of Wilson disease was made on the basis of clinical manifestations, family history, and laboratory findings and confirmed by liver biopsy. Transthoracic echocardiographic quantitative texture analysis was performed on data from the septum and left ventricular posterior wall, and mean gray level (MGL) histograms at end-diastole (d) and end-systole (s) were obtained after background correction (c). Cyclic variation index (CVI) was calculated using the formula [(cMGLd - cMGLs) / cMGLd] ×100. Results: There were no significant differences in sex, age, body mass index, heart rate or blood pressure, and conventional echocardiographic parameters between the 2 groups. The cMGLs value of the posterior wall was higher in the W group than in the C group (30.9±2.6 vs. 22.2±2.7, p=0.033). The W group had a significantly lower CVI of the septum than did the C group (-22±4.4% vs. 43.4 ±12.9%, p<0.001), and there was no significant difference in the CVI of the posterior wall (-67.0±15.9% vs. 41.7±18.6%, p=0.32). Conclusion: Abnormalities in two-dimensional echocardiographic grey-level distributions were present in Wilson disease patients. These videodensitometric myocardial alterations were significantly lower in Wilson disease patients than in the controls, and this probably represents an early stage of cardiac involvement.